Use of cultural codes when reflecting reality in the novel «The truth lives in the middle» by U. Gnilamedau - Duktava, Liubou G. (Journal of the Belarusian State University. Philology, 2025)
Cultural codes at the implicit level of a literary text represent cultural meanings associated with the values, ideals and behavioural models of a certain community (nation, population of a state). The article examines codes based on images of the borderland (middle) and the ethnic artifact of kuzhel, and notes the role of poeticisation of these images in determining the ideological orientation of U. Gnilamedau’s novel «The truth lives in the middle». With the help of images of the middle and kuzhel, the values of family, homeland, native land, choice in a polyphony of opinions, and the search for truth are shown.